Iluminasi dalam Naskah Cirebon - Achmad Opan Safari (SUHUF, 2010)
Illumination of the manuscript is an integral part of the manuscritpt itself. Illumination of the manuscript can help readers understand the origin of the manuscripts as the characteristic and pattern of the motive of the manuscripts of each region is  different from one to another, besides indeed the style and the subjectivity of the writer. One of the regions which has the manuscripts with various  illumination is Cirebon,  a  border area  between two poles of the  two big cultures: Java  and  Sunda. The tradition of making manuscript  illumination is developed in line with the tradition of the writing and rewriting the manuscripts. The illumination is made based on the contain of the text or the adjustment of the genre of the manuscript.  This writing is discussing various types of the  illumination and their functions in the manuscript and social-economic of Cirebon community.